2017
DOI: 10.1177/0892705717729017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, thermal behavior, and kinetics of degradation of alkyl hepta cyclopentyl polyhedral oligomeric silsesquioxanes/polysterene nanocomposites

Abstract: The degradation of polyhedral oligomeric silsesquioxane (POSS)/polystyrene (PS) nanocomposites at different percentages of reinforcement was studied in order to verify their thermal stability in respect to the pristine PS. Analyzed compounds were prepared by in situ polymerization of styrene, in the presence of POSSs and characterized by 1H-NMR. The temperature at 5% mass loss and the activation energy of degradation, determined through kinetics literature methods, were taken into consideration in order to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Kinetics data confirmed the key role of multiple-cage POSS in the thermo-oxidative degradation process of the obtained PS composites that let down the degradation rate, and, as demonstrated by the T5% values, enhanced the overall thermal stability of the composites. In an inert environment, the role of When we looked at our previous research regarding the kinetics of the degradation of similar PS/POSS composites but with single- [49][50][51] or double-cage structures [52,53], we observed that the slowdown in degradation kinetics for the triple-cage POSS-reinforced polystyrene was much less pronounced, about 20-30 kJ•mol −1 lower than in the systems studied in the past. This behavior could be attributed to the difficulty of obtaining multiple-cage POSS, which are sterically bulkier than single-cage POSS, to disperse themselves in the polymer matrix.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Kinetics data confirmed the key role of multiple-cage POSS in the thermo-oxidative degradation process of the obtained PS composites that let down the degradation rate, and, as demonstrated by the T5% values, enhanced the overall thermal stability of the composites. In an inert environment, the role of When we looked at our previous research regarding the kinetics of the degradation of similar PS/POSS composites but with single- [49][50][51] or double-cage structures [52,53], we observed that the slowdown in degradation kinetics for the triple-cage POSS-reinforced polystyrene was much less pronounced, about 20-30 kJ•mol −1 lower than in the systems studied in the past. This behavior could be attributed to the difficulty of obtaining multiple-cage POSS, which are sterically bulkier than single-cage POSS, to disperse themselves in the polymer matrix.…”
Section: Resultsmentioning
confidence: 89%
“…When we looked at our previous research regarding the kinetics of the degradation of similar PS/POSS composites but with single- [ 49 , 50 , 51 ] or double-cage structures [ 52 , 53 ], we observed that the slowdown in degradation kinetics for the triple-cage POSS-reinforced polystyrene was much less pronounced, about 20–30 kJ∙mol −1 lower than in the systems studied in the past. This behavior could be attributed to the difficulty of obtaining multiple-cage POSS, which are sterically bulkier than single-cage POSS, to disperse themselves in the polymer matrix.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the recent studies have focused on the preparation of organic/inorganic hybrid materials with excellent properties using inorganically developed nanoscale substances such as carbon nanotubes, graphene, and polyhedral oligomeric silsesquioxanes (POSS). 15 POSS, a class of unique inorganic compounds having a specific nanostructure, can be incorporated into polymer structures to produce hybrid materials with superior properties. 69 The general formula of POSS is showed with ( R SiO 1.5 ) n , ( n ≥ 6).…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic composites have various advantages including high-speed processability and recyclability, besides being environmentally friendly [14]. Therefore, many studies on thermoplastic composite have been completed [15,16]. However, since the matrix resin (PVDF) of thermoplastic composite has a high melt viscosity, the resin is hardly impregnated into the fibers (PAR) [14].…”
Section: Introductionmentioning
confidence: 99%